Integrasi Nilai-nilai Islam dalam Symbolic-Experiential Family Therapy Carl Whitaker Untuk Mengatasi Problematika Emosional Anak pada Keluarga Dual-Career - Andriyani, Juli; Mujiburrahman; Mahmud, Salami; Safrilsyah (At-Taujih : Bimbingan dan Konseling Islam, 2026)
Studies on children's emotional well-being in dual-career families have proliferated, yet the integration of Carl Whitaker's Symbolic-Experiential Family Therapy (SEFT) with Islamic values remains largely unexplored, particularly within the Indonesian cultural context. This study addresses this gap by constructing an integrative conceptual framework that bridges SEFT principles with Islamic epistemology as a response to children's emotional problems in dual-career families. This research employs a systematic integrative literature review method, utilizing thematic analysis of peer-reviewed articles sourced from Google Scholar, ERIC, and DOAJ databases (2013–2024), with inclusion criteria focused on family therapy, children's emotional regulation, and Islamic counseling. Findings reveal three key propositions: (1) children's emotional difficulties in dual-career families are non-deterministic and mediated primarily by the quality of parental emotional responsiveness, not merely the quantity of time; (2) Whitaker's therapeutic mechanisms authentic emotional expression, symbolic communication, and catalytic therapist involvement align structurally with Islamic principles of Siddiq (truthfulness), Amanah (parental responsibility), and Hakam (mediator) as in QS. An-Nisa [4]:35; and (3) this study contributes the SEFT-Islamic Family Counseling Framework (SIFT-Framework) a novel integrative model equipping counselors with culturally and spiritually grounded tools to restore family sakinah amid modern career pressures. This framework addresses a gap in existing Indonesian Islamic counseling literature by operationalizing the correspondence between experiential therapy and Islamic epistemology.   Keywords: Symbolic Experiential Therapy Carl Whitaker, Children's Emotional Dynamics, Dual-Career Families, Islamic Values, Integrative Framework.